2007
DOI: 10.2298/avb0706393m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estradiol or calcium treatment on mammotrophs of female middle-aged rats

Abstract: The effects of estradiol dipropionate (EDP) or calcium glucoheptonate (Ca) on the morphology and stereology of the PRL cells in 14-month-oldWistar female rats were studied. The animals were treated daily with EDP in the dose of 0.625 mg/kg b.w. or calcium glucoheptonate (Ca; 11.4 mg/kg b.w.) for two weeks. The controls were injected with vehicle alone by the same schedule. Mammotrophs (PRL cells) were immunocytochemically localized by the PAP method. Blood PRL concentration was determined by Delfia procedure. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The direct action of estrogen is enabled due to the expression of ER in almost all type of pituitary cells (64). Thus, Yin et al (65) and Milosevic et al (66) observed that estradiol provoked: PRL cell proliferation by direct action and LH secretion by positive feedback action (indirect action) in female rats. Results from our study indicated the decreased relative intensity of fluorescence and smaller volume of middle-age female rat FSH and LH cells, while PRL cells were more numerous, following estradiol treatment (0.625 mg/kg b.w.…”
Section: Does Genistein Affect Morphofunctional Parameters Of Pituitamentioning
confidence: 99%
“…The direct action of estrogen is enabled due to the expression of ER in almost all type of pituitary cells (64). Thus, Yin et al (65) and Milosevic et al (66) observed that estradiol provoked: PRL cell proliferation by direct action and LH secretion by positive feedback action (indirect action) in female rats. Results from our study indicated the decreased relative intensity of fluorescence and smaller volume of middle-age female rat FSH and LH cells, while PRL cells were more numerous, following estradiol treatment (0.625 mg/kg b.w.…”
Section: Does Genistein Affect Morphofunctional Parameters Of Pituitamentioning
confidence: 99%